2010
DOI: 10.1182/blood-2010-02-268169
|View full text |Cite
|
Sign up to set email alerts
|

When Toll-like receptor and T-cell receptor signals collide: a mechanism for enhanced CD8 T-cell effector function

Abstract: Emerging reports reveal that activating Toll-like receptor-2 (TLR2)-MyD88 signals in CD8 T lymphocytes enhances cytokine production and cytotoxicity; however, the signaling pathway remains undefined. In the present study, we examined the physiologic significance and molecular mechanisms involved in this process. We found that TLR2 engagement on T-cell receptor transgenic CD8 OT-1 T cells increased T-bet transcription factor levels consequently, augmenting effector transcript and protein levels both Introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 45 publications
4
85
1
Order By: Relevance
“…An implication is that targeting of TLR2 (44), either on the DC or on the T cell, somehow lowers the affinity threshold enabling activation of OT-I CTL. A recent report has suggested that TLR2 signaling can enhance CTL activation and effector function in response to peptide activation (53). It is tempting to speculate that in our model, TLR2 targeting on OT-I lowers the threshold of activation and promotes activation in response to low-affinity E1 and G1 APLs.…”
Section: Discussionmentioning
confidence: 68%
“…An implication is that targeting of TLR2 (44), either on the DC or on the T cell, somehow lowers the affinity threshold enabling activation of OT-I CTL. A recent report has suggested that TLR2 signaling can enhance CTL activation and effector function in response to peptide activation (53). It is tempting to speculate that in our model, TLR2 targeting on OT-I lowers the threshold of activation and promotes activation in response to low-affinity E1 and G1 APLs.…”
Section: Discussionmentioning
confidence: 68%
“…TLR2 agonists, such as Pam3CSK4, stimulate activated T cells, thus promoting their proliferation, differentiation and effector function in vitro and in vivo. [67][68][69] It has been shown that TLR2 engagement on CD8 1 T cells increased T-bet transcription in a MyD88-Akt-mTORand protein kinase C-dependent manner. 68 Consistently, Pam3CSK4 application in vivo with transferred tumor Ag-specific CD8 1 T cells results in enhanced therapeutic efficacy in tumor models.…”
Section: Activation Of Tlr-mediated Signaling Pathways Modulates Hbv-mentioning
confidence: 99%
“…[67][68][69] It has been shown that TLR2 engagement on CD8 1 T cells increased T-bet transcription in a MyD88-Akt-mTORand protein kinase C-dependent manner. 68 Consistently, Pam3CSK4 application in vivo with transferred tumor Ag-specific CD8 1 T cells results in enhanced therapeutic efficacy in tumor models. 70,71 The expression of TLR3 and TLR9 on human CD8 1 T cells was also demonstrated by some studies.…”
Section: Activation Of Tlr-mediated Signaling Pathways Modulates Hbv-mentioning
confidence: 99%
“…On top of that, activation of mTOR signaling is required to drive the costimulatory effect of TLR2 triggering to increase the production of effector molecules (36). To investigate whether these signaling pathways are also engaged during TLR-mediated bystander activation of Agexperienced T cells, we measured the phosphorylation of Akt, mTOR and the ribosomal protein S6K1 (S6), a direct target of mTORC1, by flow cytometry 30 min after stimulation with Pam3 or OVA 257-264 peptide.…”
Section: Myd88mentioning
confidence: 99%